Hadith #2527 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Malik السائب بن مالك; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) announced an expedition, and I was a very old man and I had no servant. I, therefore, sought a hireling who would serve instead of me, and I would give him his portion. So I found a man. When the time of departure arrived, he came to me and said: I do not know what would be the portions, and how much would be my portion. So offer something (as wages) to me, whether there would be any portion or not. I offered three dinars (as his wages) for him. When some booty arriv
Grade: Sahih

Hadith #3045 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; al-Sa'ib bin Malik السائب بن مالك; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
‘Urwa bin Al Zubair said “Hisham bin Halim bin Hizam found a man who was the governor of Hims making some Copts stand in the sun for the payment of jizyah. He said “What is this?” I heard the Apostle (ﷺ) as saying “Allaah Most High will punish those who punish the people in this world.”
Grade: Sahih

Hadith #5063 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Malik السائب بن مالك; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
should I not tell you about me and about Fatimah, daughter of the Messenger of Allah (May peace be upon him). She was dearest to him of his family. When she was with me, she pulled mill-stone which affected her hand; she carried water with the water-bag which affected the upper portion of her chest: She swept the house so much so that her clothes became dusty; and she cooked food by which her clothes became black, and it harmed her. We heard that some slaves had been brought to the prophet (May
Grade: Da'if